'I have a picture of the Monster!': Il mostro di Frankenstein and the search for Italian horror cinema. Issue 2 (1st March 2017) - Hunter, Russ
Typically accounts of Italian horror cinema have highlighted the production and release of Riccardo Freda's I vampiri (Lust of the Vampire) in the late 1950s as marking the beginning of Italian engagement with the horror genre. The logic that follows is often that the nature of fascist censorship impeded any explorations of the genre in the 1920s and 1930s and that in the post war period it was only the commercial success of Hammer Horror that tempted Italian producers to venture into horror film-making. In this way Italian horror cinema is considered to have no antecedents and is frequently seen in relation to its readiness to ape production successes elsewhere. Increasingly, however, Il mostro di Frankenstein (The Monster of Frankenstein) (Testa, 1921) is being identified as Italy's 'first' horror film. Yet as a lost film that has left little material trace, evidence of its generic position is, at best, ambiguous. This article will examine a heretofore underexplored and obscure film in order to interrogate the extent to which it can be seen as Italy's earliest engagement with horror production. In so doing it allow us to see much more complex and nuanced developments of the history of both Italian and European horror cinema, challenging previous assumptions about the history of the genre as a whole.